PENGARUH BAKAT POTENSI KEWIRAUSAHAAN DAN METODE PEMBELAJARAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Rumijati, Aniek (Journal of Innovation in Business and Economics, 2010)
This study aims to describe the talent and entrepreneurship that have the potential students, teaching methods courses in entrepreneurship, student interest in entrepreneurship and know the effect of entrepreneurial talent and potential and methods of interest in entrepreneurship students. The analysis tool used is the range of scale and multiple linear regression. Results obtained findings that entrepreneurial talent and competence of students is very high, both entrepreneurial learning methods and student interest in entrepreneurship is very high. Entrepreneurial talent and potential has the strongest influence on student interest in entrepreneurship than learning methods, while learning method had no significant effect.